2015 IEEE International Advance Computing Conference (IACC) 2015
DOI: 10.1109/iadcc.2015.7154832
|View full text |Cite
|
Sign up to set email alerts
|

Reducing power consumption of smart device by proper management of Wakelocks

Abstract: Smart devices offer plenty of applications which are very power consuming. Number of applications running on smart devices and users are increasing day by day, but battery capacity is not improving with the same pace. This paper describes the implementation of android based Wakelock Tracking and Releasing System (WTRS) that can be used for reducing power consumption on android devices. The WTRS system detects improper behavior of buggy wakelock and releases them in real time environment. The main aim of the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Previous work has been done to measure and model the energy consumed by various phone components such as the CPU [ 18 , 19 , 20 , 21 , 22 ], memory [ 18 , 23 ], WiFi NIC [ 18 , 19 , 20 , 21 , 24 ], display screen [ 24 ], GPS sensor [ 2 , 11 ], Bluetooth module [ 25 , 26 , 27 ], cellular module [ 25 ], and so on.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has been done to measure and model the energy consumed by various phone components such as the CPU [ 18 , 19 , 20 , 21 , 22 ], memory [ 18 , 23 ], WiFi NIC [ 18 , 19 , 20 , 21 , 24 ], display screen [ 24 ], GPS sensor [ 2 , 11 ], Bluetooth module [ 25 , 26 , 27 ], cellular module [ 25 ], and so on.…”
Section: Related Workmentioning
confidence: 99%
“…Because a phone in the basic state runs no applications, keeps Bluetooth/GSM/3G radios disabled and camera/microphone/speakers off, the energy consumed by the other components (e.g., sensors, cameras, Bluetooth modules and cellular modules) is zero and not involved in our model. Compared to our work, the work mentioned in Section 2.2 does not aim to model the energy of the phone in the basic state, and the models are for different phone components [ 2 , 11 , 25 , 26 , 27 ] or for individual components [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ], rather than the entire phone.…”
Section: Related Workmentioning
confidence: 99%
“…Pathak et al [43] observed that 70% of energy bugs are the result of wake lock related problems. This is no wonder that much research [44,6,35,8,53,46] has been conducted to characterize, detect, and minimize no sleep bugs so that the developers can optimize their code.…”
Section: Energy Optimization and Guidelinesmentioning
confidence: 99%
“…Pathak et al [43] observed that 70% of energy bugs are the result of wake lock related problems. This is no wonder that much research [44,6,35,8,53,46] has been conducted to characterize, detect, and minimize no sleep bugs so that the developers can optimize their code.…”
Section: Energy Optimization and Guidelinesmentioning
confidence: 99%